Nanocomposites Based on Waterborne Polyurethane Matrix and Fe3O4 Nanoparticles: Synthesis and Characterization - Meiorin, Cintia; Scherzer, Selina L.; Mucci, Veronica; Actis, Daniel G.; Zelis, Pedro Mendoza; Schubert, Dirk W.; Mosiewicki, Mirna A.; Aranguren, Mirta (Advanced Engineering Materials, 2021)
Herein, the feasibility of producing waterborne polyurethane nanocomposites containing magnetic nanoparticles (MNPs) by casting method, to obtain films with potential magnetic properties, is shown. The characterization of the resulting nanocomposites is carried out using infrared spectroscopy, thermal analysis, colorimetry, tensile tests, microscopy and magnetic tests. The films become opaque and dark colored when MNP is incorporated. The mechanical behavior of the nanocomposites is that of tough plastics, with Young's modulus in the range of 106-143 MPa, increasing with the MNP concentration. Aggregation of the MNP takes place at concentrations above 1.5 wt%, as observed in scanning electron microscopy (SEM) images of the fracture surfaces. Magnetization saturation increases with the concentration of MNP. A small coercivity indicates the presence of a fraction of blocked particles whose size exceeds the critical size for superparamagnetism at the temperature of the measurements.
CRIS-Team WoS Importer:2021-08-13